Analisis Stres Kerja, Lingkungan Kerja, Motivasi dan Kompensasi dalam Mempengaruhi Produktivitas Karyawan - Muhammad Erick Saputra; Andiana Rosid; Suwarto (Universitas Muhammadiyah Metro, 2026)
The low level of employee productivity can have a negative impact on the company such as lazy work, lack of work performance, and employee discipline. Employee productivity is basically influenced by certain conditions, namely conditions originating from within the individual called individual factors such as motivation and work stress and conditions originating from outside the individual called situational factors such as work environment and compensation. The purpose of this study was to analyze the effect of work stress, work environment, motivation, compensation on employee productivity at PT. Bima Finance Metro City. The research design is quantitative research or verification research. The method used in this research is the explanatory survey method. The objects in this study are work stress, work environment, motivation, compensation, employee productivity. This research at PT. Bima Finance Metro City with 34 respondents The analytical tool used is data quality analysis and multiple linear regression analysis with SPSS program. The results showed that partially work stress, work environment, motivation, compensation had a positive and significant effect on employee productivity. Simultaneously work stress, work environment, motivation, compensation simultaneously have a significant effect on employee productivity, with motivation with the greatest influence on employee productivity.